Climate and soils together regulate photosynthetic carbon isotope discrimination within C3 plants worldwide. Issue 9 (30th October 2018) - Cornwell, William K.; Wright, Ian J.; Turner, Joel; Maire, Vincent; Barbour, Margaret M.; Cernusak, Lucas A.; Dawson, Todd; Ellsworth, David; Farquhar, Graham D.; Griffiths, Howard; Keitel, Claudia; Knohl, Alexander; et al.
Abstract: Aim: Within C3 plants, photosynthesis is a balance between CO2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO2 drawdown during photosynthesis. Location: Global Time period: 1951–2011. Major taxa studied: Vascular plants. Methods: We assembled a database of leaf carbon isotope ratios containing 3, 979 species–site combinations from across the globe, including 3, 645 for C3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results: The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO2 concentrations at the site of carboxylation among plants in a given soil and climate.